2011
DOI: 10.5761/atcs.oa.09.01514
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Permanent Neurologic Dysfunction and Mortality after Total Arch Replacement with Separate Arch Vessel Grafting Using Selective Cerebral Perfusion

Abstract: Objectives: The present study was undertaken to identify risk factors for permanent neurological dysfunction (PND) and in-hospital mortality after total aortic arch replacement (TAR) with separate arch vessel grafting using selective cerebral perfusion (SCP) and hypothermic circulatory arrest. Methods: Between 1998 and 2008, we preformed a TAR on 143 consecutive patients in two centers by identical methods. Of these, 19 (13.3%) were emergency operations, and 46 (32.2%) were open stent-graft placements. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…These numbers are comparable with data published in the literature [9] showing that also low-volume centre can achieve acceptable results in terms of all-cause mortality. Percentage of patients with permanent or temporary neurological deficit was slightly higher, than reported in the recent literature.…”
Section: Discussionsupporting
confidence: 90%
“…These numbers are comparable with data published in the literature [9] showing that also low-volume centre can achieve acceptable results in terms of all-cause mortality. Percentage of patients with permanent or temporary neurological deficit was slightly higher, than reported in the recent literature.…”
Section: Discussionsupporting
confidence: 90%
“…Would arch vessel reconstruction correlate to development of neurologic dysfunction during the reconstruction? A history of neurologic events, 22 older age, 23 or urgency 24 has been shown to be a significant risk factor for intraoperative neurologic events under SCP. However, a multicenter study investigating brain protection using SCP demonstrated that the duration of cerebral perfusion had no impact on neurologic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Because the duration of hypothermic circulatory arrest and increasing age are important predictors of temporary neurologic dysfunction and of fine-motor and memory deficits after aortic arch surgery, reducing the duration of circulatory arrest should reduce the prevalence of these complications [20]. Lastly, while some authorities find it controversial to perform SABP in patients with acute type A dissection due to a higher risk of neurological complications, a number of very recent studies that have shown SABP for acute type A aortic dissection provides acceptable results [21-24]. …”
Section: Discussionmentioning
confidence: 99%